A self-power flexible piezoelectric sensing system for badminton training monitoring - Wang, C.; Fan, Z.; Feng, K. (IEICE Electronics Express, 2021)
Monitoring of training, especially the use of soft devices, is difficult but has become more and more important for human health. In this paper, a self-power flexible piezoelectric sensing system for badminton training based on polyvinylidene fluoride (PVDF) piezoelectric film sensoris designed and experimentally verified. The sensing array is divided as 3 x 3 chessboard-like areas, which contain thin-film transductors to determine the hitting position and force. The system owns a linear relationship between force and generated electric signal with a sensitivity of 0.377 V/N and the minimum sampling interval of 1s. Furthermore, the piezoelectric Lead Zirconium titanite (PZT) patch behind the racket isemployed as a power source to support the sensing circle. This work paves a new way for the application of artificial intelligence in the human health area and the Internet of Things.